Application of micro-computers in chemical engineering education - Fawzi B.Y. Nakkash (1983)
As micro-computers are now widely available, they are being used increasingly for educational purposes. Three types of programs may be distinguished: self-contained programs, interactive programs, and simulation programs. [Continues.]